The Business Ethics Workshop - Brusseau, James; Open Textbook Library (Open Textbook Library, 2012)
Ethics is about determining value; it's deciding what's worth doing and what doesn't matter so much.Business ethics is the way we decide what kind of career to pursue, what choices we make on the job,which companies we want to work with, and what kind of economic world we want to live in and thenleave behind for those coming after. There are no perfect answers to these questions, but there's adifference between thinking them through and winging it. The Business Ethics Workshop provides aframework for identifying, analyzing, and resolving ethical dilemmas encountered through working life.
Chapter 1: What Is Business Ethics? -- Chapter 2: Theories of Duties and Rights: Traditional Tools for Making Decisions in Business When the Means Justify the Ends -- Chapter 3: Theories of Consequence Ethics: Traditional Tools for Making Decisions in Business when the Ends Justify the Means -- Chapter 4: Theories Responding to the Challenge of Cultural Relativism -- Chapter 5: Employee's Ethics: What's the Right Job for Me? -- Chapter 6: Employee's Ethics: Getting a Job, Getting a Promotion, Leaving -- Chapter 7: Employee's Ethics: Making the Best of the Job You Have as You Get from 9 to 5 -- Chapter 8: Manager's Ethics: Getting, Promoting, and Firing Workers -- Chapter 9: Manager's Ethics: Deciding on a Corporate Culture and Making It Work -- Chapter 10: The Tense Office: Discrimination, Victimization, and Affirmative Action -- Chapter 11: The Aroused Office: Sex and Drugs at Work -- Chapter 12: The Selling Office: Advertising and Consumer Protection -- Chapter 13: The Responsible Office: Corporations and Social Responsibility -- Chapter 14: The Green Office: Economics and the Environment -- Chapter 15: The Domination Office: The Star System and Labor Unions
In English.
Description based on online resource
Keywords: Business -- Textbooks